2018
DOI: 10.3390/polym10080856
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique for Fiber Formation: Mechanotropic Spinning—Principle and Realization

Abstract: We present basic experimental data and the theoretical background of a novel technique for fiber spinning from polymer solutions. The principal feature of the advanced process is realization of phase separation with detachment of a solvent, accompanied by the orientation of macromolecules, under the action of high extension rates. This is similar in some respects to dry spinning, though the driving force is not diffusion with subsequent evaporation of a solvent but redistribution of polymer-solvent interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 80 publications
(88 reference statements)
1
42
0
Order By: Relevance
“…This behavior is consistent with the behavior of the filaments of polymer solutions under extension [ 25 ]. It has been found that threads formed by solutions of flexible-chain polymers can show exponential thinning, which is further replaced by the emergence of blistering structures and, as a result, a fiber is formed [ 26 , 27 , 28 , 29 ]. Exponential thinning is associated with the unfolding of polymer chains along the stretching axis [ 30 ] and the blistering mechanism can be attributed to the flow-induced phase separation under extension [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is consistent with the behavior of the filaments of polymer solutions under extension [ 25 ]. It has been found that threads formed by solutions of flexible-chain polymers can show exponential thinning, which is further replaced by the emergence of blistering structures and, as a result, a fiber is formed [ 26 , 27 , 28 , 29 ]. Exponential thinning is associated with the unfolding of polymer chains along the stretching axis [ 30 ] and the blistering mechanism can be attributed to the flow-induced phase separation under extension [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…As is seen from these data, only when the polymer concentration is above 12–15% the values of the Newtonian viscosity reach 100 Pa·s and at 23% the viscosity approaches 1000 Pa·s. In other words, both strategies, i.e., an increase in the molecular weight of the polymer or concentration of the pre-polymer solution do not allow producing of the dopes with viscoelastic properties suitable for dry-wet or mechanotropic spinning [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…1-a fiber-optic illuminator along the jet axis; 2-back lighting; 3-a syringe with the solution; 4-a lens to focus the light into the center of an extended jet; 5-a camera; 6-a jet. This is according to [30,31].…”
Section: Modeling Of Mechanotropic Spinningmentioning
confidence: 99%
“…The corresponding experimental results are presented in Figure 15. The images show the comparative kinetics of the thinning of the liquid filament and the phase separation process according to the mechanism described in detail in [30,31]. For a PAN solution, a noticeable change in the shape of the jet begins from the 30th second and is accompanied by the release of solvent to the jet surface.…”
Section: Modeling Of Mechanotropic Spinningmentioning
confidence: 99%